2012
DOI: 10.2298/abs1201145k
|View full text |Cite
|
Sign up to set email alerts
|

The potential of four woody species for the revegetation of fly ash deposits from the ‘Nikola Tesla-a’ thermoelectric plant (Obrenovac, Serbia)

Abstract: Four woody species, Tamarix tentandra Pallas, Populus alba L. and Robinia pseudoacacia L. (planted) and Amorpha fruticosa L. (naturally colonized) were studied at two fly ash deposit lagoons, weathered 3 (L1) and 11 years (L2). All species were assessed in terms of their invasive ability, photosynthetic efficiency, photosynthetic pigments and damage symptoms, while the characteristics of the habitat were assessed in terms of trace element content and the pH and EC of the ash. A reduced vitality of all po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The sap osmotic potential was the most favorable in Crepis setosa, Cirsium arvense and Verbascum phlomoides (from −0.981 MPa to −1.135 MPa) whereas in Populus alba unfavorable sap osmotic value was detected (−1.377 MPa) (Pavlović et al, 2004) ( Table 4). Decrease of chlorophylls and carotenoids content in plants growing on fly ash deposits were noted in Ricinus communis, Typha latifolia, Thelypteris dentate, Festuca rubra, Amorpha fruticosa, Tamarix tetandra, Populus alba and Robinia pseudoaccacia (Kostić et al, 2012;Kumari et al, 2013;Pandey, 2013;Gajić et al, 2016) in relation to control (Table 4). Furthermore, in Cicer arietinum which grew in fly ash treated soils, the content of chlorophylls decreased at 50 and 100% fly ash whereas carotenoids amount increased (Pandey et al, 2010) (Table 4).…”
Section: Plant Physiological Adaptation On Fly Ashmentioning
confidence: 96%
See 2 more Smart Citations
“…The sap osmotic potential was the most favorable in Crepis setosa, Cirsium arvense and Verbascum phlomoides (from −0.981 MPa to −1.135 MPa) whereas in Populus alba unfavorable sap osmotic value was detected (−1.377 MPa) (Pavlović et al, 2004) ( Table 4). Decrease of chlorophylls and carotenoids content in plants growing on fly ash deposits were noted in Ricinus communis, Typha latifolia, Thelypteris dentate, Festuca rubra, Amorpha fruticosa, Tamarix tetandra, Populus alba and Robinia pseudoaccacia (Kostić et al, 2012;Kumari et al, 2013;Pandey, 2013;Gajić et al, 2016) in relation to control (Table 4). Furthermore, in Cicer arietinum which grew in fly ash treated soils, the content of chlorophylls decreased at 50 and 100% fly ash whereas carotenoids amount increased (Pandey et al, 2010) (Table 4).…”
Section: Plant Physiological Adaptation On Fly Ashmentioning
confidence: 96%
“…Successful ecorestoration is achieved by establishment of the self-sustaining vegetation cover through human intervention by seeding the mixture of grasses and legumes, and planting shrubs and trees (Pavlović et al, 2004;Mitrović et al, 2008;Kostić et al, 2012;Maiti, 2013;Gajić et al, 2016). In a temperate climate, grass and legume species that are the best for the revegetation of degraded sites belong to the genus of Festuca, Lolium, Agropyron, Poa, Medicago, and Vicia whereas the trees that provide good phytostabilization of substrates are Poplar, Robinia, Salix, Alnus, Betula, and Acer (Prasad, 2006).…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In May and June, with the peak of the flood wave, the highest concentrations of Mn, Pb, Cd, Co, As and B were recorded. The study of Kostić et al (2012) indicated that majority of those elements are common for fly ash disposal field of power plant "Nikola Tesla". This leads to an assumption that flooding of the fly ash disposal field and its intensive rinsing by rainfall could be the reason for increased concentrations of metals and metalloids and observed correlations with water level.…”
Section: Pollution Pressures At the Studied Sitementioning
confidence: 99%
“…9 Woody plants with large cover and high biomass may have an important role in the process of revegetation of waste deposits. 10 Furthermore, organic matter originating from plants could be of great importance in the process of soil humification where phenolic compounds are very significant. 11,12 Allelopathy presents interactions between plants through the action of allelochemicals.…”
Section: Introductionmentioning
confidence: 99%